Organic–inorganic metal halide hybrids beyond perovskites. Issue 10 (3rd October 2018) - Zhou, Chenkun; Lin, Haoran; Lee, Sujin; Chaaban, Maya; Ma, Biwu
ABSTRACT: Organic–inorganic metal halide hybrids have emerged as new generation functional materials with exceptional structure and property tunability for a variety of applications. Besides the most investigated ABX3 metal halide perovskites, a variety of hybrids consisting of a wide range of organic cations and metal halide anions have been developed and studied recently. Here, we provide an overview of these new materials possessing various crystallographic structures, including double perovskites, low dimensional hybrids, and other perovskite-related materials. We discuss their syntheses, functional properties, and optoelectronic applications. Challenges and opportunities are then laid out for these hybrid materials beyond perovskites. GRAPHICAL ABSTRACT: IMPACT STATEMENT: By choosing appropriate organic cations and metal halide anions, single crystalline ionically bonded hybrid materials can be assembled to possess various structures beyond the well-known ABX3 perovskite. These hybrid materials exhibit exciting new properties with potential applications in a variety of areas.